The complete chloroplast genome sequence of Sloanea sinensis. Issue 2 (1st February 2021) - Weng, Yuhao; Ye, Daiquan; You, Yunfei; Chen, Yitang; Fan, Fujin; Shi, Jisen; Chen, Jinhui
Abstract: Sloanea sinensis (Hance) Hu is a tree species and member of the Elaeocarpaceae family. It's an excellent commercial tree species which has a relatively high net growth as forests. Here, we report the complete chloroplast genome sequence of a Sloanea genus for the first time. The complete chloroplast sequence of S. sinensis is 158, 001 bp in length, including a large single copy region (LSC: 88, 481 bp) and a small single copy region (SSC: 17, 481 bp), the latter of which is separated by a pair of inverted repeat regions (IRs: 26, 051 bp). Phylogenetic analysis indicates that the Elaeocarpaceae is a family within the Oxalidales may be more appropriate than belongs to Malvales as traditional plant taxonomy.